Relationship Between the Arrangement of Oxide Ion Vacancies and Oxide Ion Conduction in Ba2(Fe0.9In0.1)2O5 + δ. Issue 6 (15th April 2016) - Fujishiro, Fumito; Kadota, Dai; Hashimoto, Takuya
Abstract : To evaluate the relationship between arrangement of oxide ion vacancies and oxide ion conduction in a mixed ionic–electronic conductor Ba2 (Fe0.9 In0.1 )2 O5+δ, we studied temperature dependences of electrical conductivity and the crystal structure including the oxide ion vacancies using high‐temperature X‐ray diffraction, thermogravimetry–differential thermal analysis‐mass spectroscopy, and electrical conductivity measurements with four‐probe method. The sample's crystal structure was observed to be of a perovskite type with a partial ordering of oxide ion vacancies below 600°C. Increasing the temperature above 600°C led to associative O2 desorption and complete randomization of the arrangement of oxide ion vacancies to form a cubic phase. The electrical conductivity of the sample under N2 flow showed an Arrhenius‐type behavior with two trends against temperature. Activation energies were estimated as 0.61 eV below 600°C and 0.27 eV above 600°C. The lower value of 0.27 eV showed fairly good agreement with that of activation energy for oxygen permeation fluxes in this material. It was concluded that the fully random distribution of oxide ion vacancies led to improved oxide ion migration in Ba2 (Fe0.9 In0.1 )2 O5+δ .